Development of SHEQTM Management System for Construction Industry in Malaysia - Ikhsan, Mohd Mukhtar (2005)
The objectives of the study are: to review the existing management standards on health and safety (OHSAS 18001: 1999), environmental (ISO 14001:1996) and quality (ISO 9001:1994); to study the correspondences data between these three management systems; to develop a guideline of SHEQTM Integrated Management System; to analyze and study the pro and con of the proposed guidelines.